Composite diaphragm as well as preparation method and application thereof
The composite diaphragm structure of the composite alumina layer and the polymer layer solves the problem of battery runaway at high temperatures, achieves higher safety and thermal conductivity, and reduces the risk of thermal runaway.
Patent Information
- Application Number
- CN202511265555.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-09-05
AI Technical Summary
Existing battery separators are prone to runaway under high temperature conditions, leading to safety risks such as thermal runaway, fire, and explosion. In addition, their thermal conductivity is insufficient and they cannot effectively prevent short circuits.
A composite diaphragm structure of a composite alumina layer and a polymer layer is adopted. The composite alumina layer includes an intermediate aluminum foil and a porous alumina layer. The intermediate aluminum foil has through holes, and the porous alumina layer has heat conduction properties. The polymer layer melts and closes the holes at high temperatures to form a thermal blockade, preventing the battery from continuing to lose control.
The battery's temperature resistance, high-temperature dimensional stability and thermal conductivity are improved, the probability of thermal runaway is reduced, and the battery's safety is enhanced.
Smart Images

Figure CN120810186A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular to a composite diaphragm, a preparation method and application thereof, and more particularly to a composite diaphragm, a preparation method, a battery, a battery pack and an electric device. BACKGROUND
[0002] The diaphragm is a core component in a battery, and directly determines the safety of the battery. It is known that the safety risk of the battery mainly originates from the uncontrollability of the high energy density and the internal chemical reaction of the battery, and especially under certain conditions (such as short circuit, high temperature, etc.), heat runaway, fire, explosion and other serious consequences can be caused. Therefore, improving the temperature resistance, high-temperature dimensional stability and heat dissipation performance of the diaphragm is one of the key problems that need to be solved and the most important research direction at present. SUMMARY
[0003] The present application aims to at least solve one of the technical problems in the related art. To this end, the present application provides a composite diaphragm with good temperature resistance, high-temperature dimensional stability and heat dissipation performance, as well as a preparation method and application thereof.
[0004] In a first aspect, the present application provides a composite diaphragm. According to an embodiment of the present application, the composite diaphragm comprises a composite aluminum oxide layer, the composite aluminum oxide layer comprising: an intermediate aluminum foil, the intermediate aluminum foil having a through hole; and a porous aluminum oxide layer, the porous aluminum oxide layer being located on at least one side of the intermediate aluminum foil. In the composite diaphragm, the pores in the porous aluminum oxide layer and the through hole in the intermediate aluminum foil can form an active ion transmission channel, the porous aluminum oxide layer has heat conduction performance, and the structure is continuous, and there is basically no problem of powder falling off, and can play a role in supporting the framework. Even under high-temperature runaway, the porous aluminum oxide layer still maintains the role of the framework, has good heat resistance and high-temperature dimensional stability, and can effectively prevent short circuit. The intermediate aluminum foil can play a superior heat conduction ability, increase the heat conduction characteristics of the diaphragm, prolong the heat runaway time, and reduce the probability of battery heat runaway, thereby effectively improving the safety of the battery using the composite diaphragm.
[0005] According to an embodiment of the present application, the composite diaphragm further comprises: a polymer layer, the polymer layer being stacked with the composite aluminum oxide layer.
[0006] According to an embodiment of the present application, the material of the polymer layer comprises at least one of polyethylene, polypropylene, aramid, polyvinylidene fluoride, cellulose, polyethylene terephthalate, polyimide and non-woven fabric.
[0007] According to an embodiment of the present application, the polymer layer is located on one side of the composite aluminum oxide layer.
[0008] According to an embodiment of the present application, the polymer layer is located on opposite sides of the composite alumina layer.
[0009] According to an embodiment of the present application, the material of the polymer layer on one side of the composite alumina layer is polyethylene, and the material of the polymer layer on the other side of the composite alumina layer is polypropylene.
[0010] According to an embodiment of the present application, the composite alumina layer is located on opposite sides of the polymer layer.
[0011] According to an embodiment of the present application, the composite alumina layer comprises pores, the pores comprising large pores and small pores, the small pores being located in the porous alumina layer, and the large pores penetrating through the intermediate aluminum foil or penetrating through the porous alumina layer on one side of the intermediate aluminum foil and deep into the intermediate aluminum foil, the diameter φ1 of the large pores and the diameter φ2 of the small pores satisfying: φ2 < φ1.
[0012] According to an embodiment of the present application, the composite separator satisfies at least one of the following conditions: The diameter φ1 of the large pores is 5 μm to 50 μm; The diameter φ2 of the small pores is 20 nm to 5 μm; The gap I1 between adjacent two large pores is 5 μm to 50 μm; The gap I2 between adjacent two small pores is 30 nm to 1 μm; The coverage L1 of the large pores is 5% to 50%; The coverage L2 of the small pores is 5% to 60%; The depth H1 of the large pores is the sum of the thickness of the intermediate aluminum foil and the thickness of the porous alumina layer on one side, or the thickness of the intermediate aluminum foil, specifically, H1 is 0.5 μm to 5 μm; The depth H2 of the small pores is the thickness of the porous alumina layer on one side, specifically, H2 is 0.2 μm to 5 μm.
[0013] According to an embodiment of the present application, a functional material is arranged in the pores, the functional material comprising at least one of a solid-state electrolyte, a lithium supplement material, an organic polymer, and a binder.
[0014] According to an embodiment of the present application, the functional material satisfies at least one of the following conditions: The solid-state electrolyte comprises lithium titanium aluminum phosphate; The lithium supplement material comprises at least one of Li6CoO4, Li5FeO4, Li2C2O4, and Li2NiO2; The organic polymer comprises at least one of polyethylene, polypropylene, polyvinylidene fluoride, and polymethyl methacrylate; The binder comprises a granular binder.
[0015] According to an embodiment of the present application, the composite separator satisfies at least one of the following conditions: The thickness of the composite separator is 3 μm to 20 μm; The thickness of the polymer layer is 2 μm to 22 μm; The porosity of the polymer layer is 20% to 70%; The thickness of the intermediate aluminum foil is 0.5 μm to 3 μm; The thickness of the porous aluminum oxide layer is 0.3 μm to 2.5 μm.
[0016] According to a second aspect of the present application, a method for preparing the composite separator described above is provided. According to an embodiment of the present application, the method comprises: anodizing an aluminum foil, forming an oxide layer on at least one side surface of the aluminum foil, and obtaining an anodization product; and performing pore-forming treatment on the surface of the anodization product, and obtaining a composite aluminum oxide layer. Specifically, by anodizing, a porous aluminum oxide layer with small pores can be formed on at least one side surface of the aluminum foil, and by further performing pore-forming treatment, large pores can be formed, and then by combining the large pores and the small pores, a transmission channel for active ions can be formed in the composite aluminum oxide layer, and meanwhile, part of the aluminum foil that has not been oxidized constitutes an intermediate aluminum foil. Thus, the method is simple to operate, and the composite separator obtained has better temperature resistance and high-temperature dimensional stability, and the battery using the composite separator has higher safety.
[0017] According to an embodiment of the present application, the anodizing satisfies at least one of the following conditions: The electrolytic solution for the anodizing comprises at least one of oxalic acid, phosphoric acid, and sulfuric acid; The cathode for the anodizing comprises a platinum electrode; The current density for the anodizing is 1 A / dm 2 ~ 5 A / dm 2 ; The temperature for the anodizing is 0°C to 60°C; The time for the anodizing is 10 min to 10 h.
[0018] According to an embodiment of the present application, the pore-forming treatment comprises at least one of chemical etching, focused ion beam etching, and laser drilling.
[0019] According to an embodiment of the present application, the pore-forming treatment satisfies at least one of the following conditions: The ion beam current for the focused ion beam etching is 1 pA to 50 pA; The residence time for the focused ion beam etching is 50 μs to 1000 μs; The laser frequency used in the laser drilling is 100 Hz to 1000 Hz. The drilling speed of the laser drilling is 0.5 m / min to 5 m / min.
[0020] According to an embodiment of the present application, the method further comprises depositing a functional material into the pores of the composite alumina layer.
[0021] According to an embodiment of the present application, the deposition method comprises chemical vapor deposition.
[0022] According to an embodiment of the present application, the method further comprises compounding the composite alumina layer and the polymer layer.
[0023] According to an embodiment of the present application, the compounding comprises stacking the composite alumina layer and the polymer layer, and pressing the obtained stack product to make it compound.
[0024] In a third aspect, the present application provides a battery. According to an embodiment of the present application, the battery comprises the composite separator as described above or the composite separator prepared by the method as described above. The probability of short circuit and thermal runaway of the battery is significantly reduced, and the battery has high safety.
[0025] In a fourth aspect, the present application provides a battery pack. According to an embodiment of the present application, the battery pack comprises the composite separator as described above, the composite separator prepared by the method as described above, or the battery as described above. The battery pack has better safety performance.
[0026] In a fifth aspect, the present application provides an electric device. According to an embodiment of the present application, the electric device comprises the composite separator as described above, the composite separator prepared by the method as described above, the battery as described above, or the battery pack as described above. The electric device has all the features and advantages of the battery as described above or the battery pack as described above, which will not be repeated here. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 is a structural schematic diagram of a composite separator according to an embodiment of the present application.
[0028] Figure 2 is a structural schematic diagram of a composite separator according to another embodiment of the present application.
[0029] Figure 3 is a structural schematic diagram of a composite separator according to another embodiment of the present application.
[0030] Figure 4 is a structural schematic diagram of a composite separator according to another embodiment of the present application.
[0031] Figure 5is a structural schematic diagram of a composite separator according to another embodiment of the present application. DETAILED DESCRIPTION
[0032] Embodiments of the present application are described in detail below with reference to examples shown in the accompanying drawings. The embodiments described below by reference to the accompanying drawings are exemplary and are intended to explain the present application, and cannot be understood as a limitation of the present application.
[0033] The present application is based on the discovery and realization of the inventors on the following facts and problems: At present, in order to improve the high-temperature resistance and high-temperature dimensional stability of the separator, generally, inorganic ceramic material is coated on both sides of the polymer separator to form a ceramic composite separator. Although the heat resistance of inorganic ceramic improves the high-temperature deformation resistance and high-temperature dimensional stability of the separator, since the ceramic layer is generally composed of ceramic particles, the ceramic particles are bonded by the adhesive, and the problem of powder falling off is easy to occur; at the same time, according to the energy density requirement, in order to reduce the thickness of the separator, single-sided ceramic is now widely used, but when the environmental humidity changes, the single-sided ceramic causes short circuit due to the problems of water absorption or water loss of the single-sided ceramic, in addition, the separator in the related art has poor heat conduction performance under high temperature, which cannot well guarantee the thermal safety. Based on the above problems, the inventors of the present application propose a composite separator with good high-temperature resistance, good high-temperature dimensional stability, and excellent heat conduction performance.
[0034] Therefore, in a first aspect, the present application provides a composite separator. According to embodiments of the present application, with reference to Figure 1 The composite separator includes a composite aluminum oxide layer 10, the composite aluminum oxide layer 10 includes: an intermediate aluminum foil 11, the intermediate aluminum foil has a through hole; a porous aluminum oxide layer 12, the porous aluminum oxide layer 12 is located on at least one side of the intermediate aluminum foil 11, Figure 1 The intermediate aluminum foil is provided with the porous aluminum oxide layer 12 on both sides. In the composite separator, the porous aluminum oxide layer has heat conduction performance and continuous structure, and basically does not have the problem of powder falling off, and can play a role of skeleton support. Even under high temperature out of control, the porous aluminum oxide layer still maintains the skeleton function, has good heat resistance and high-temperature dimensional stability, can effectively prevent short circuit, and the intermediate aluminum foil can play a superior heat conduction ability, increase the heat conduction characteristics of the separator, prolong the thermal runaway time, and reduce the probability of thermal runaway of the battery, thereby effectively improving the safety of the battery using the composite separator.
[0035] According to the embodiments of the present application, the composite diaphragm further comprises a polymer layer 20 which is stacked with the composite alumina layer 10. Thus, by setting the polymer layer, when the battery temperature rises, the polymer layer can melt the closed pores to form a thermal block, prevent the battery from continuing to run out of control, and further improve the safety of the battery. Moreover, the polymer layer has better hydrophobic performance, so that the composite diaphragm itself has excellent hydrophobic effect.
[0036] According to the embodiments of the present application, the material of the polymer layer is not particularly limited, as long as it can meet the use requirements of the diaphragm. In some embodiments, the material of the polymer layer includes at least one of polyethylene, polypropylene, aramid, polyvinylidene fluoride, cellulose, polyethylene terephthalate, polyimide, and non-woven fabric. Thus, the heat resistance is better, the closed pore temperature is higher, and the material source is extensive and the cost is lower.
[0037] According to the embodiments of the present application, the specific stacking mode of the polymer layer 20 and the composite alumina layer 10 is not particularly limited, and the number of the polymer layer 20 and the composite alumina layer 10 is also not particularly limited, which can be flexibly selected according to actual needs.
[0038] In some embodiments, referring to Figure 2 , the polymer layer 20 is located on one side of the composite alumina layer 10. Thus, by setting the polymer layer, when the battery temperature rises, the polymer layer can melt the closed pores to form a thermal block, prevent the battery from continuing to run out of control, and further improve the safety of the battery. Moreover, the polymer layer has better hydrophobic performance, so that the composite diaphragm itself has excellent hydrophobic effect.
[0039] In some embodiments, referring to Figure 3 , the polymer layer 20 is located on the opposite sides of the composite alumina layer 10. Thus, the stress on both sides of the composite diaphragm is uniform, which can effectively improve the curling problem of the diaphragm. At the same time, a thermal block is formed to prevent the battery from continuing to run out of control, further improve the effect of improving the safety of the battery, and the composite diaphragm has excellent hydrophobic performance on both sides.
[0040] According to the embodiments of the present application, when the composite diaphragm is provided with polymer layers on both sides of the composite alumina layer, the material of the polymer layer on one side of the composite alumina layer is polyethylene, and the material of the polymer layer on the other side of the composite alumina layer is polypropylene. Specifically, in the battery, the potential and temperature of the positive plate are higher than those of the negative plate. By setting the composite diaphragm to be polypropylene on one side and polyethylene on the other side, the polypropylene has more excellent oxidation resistance, and under the use condition, the polypropylene diaphragm is set to face the positive plate, which can effectively improve the problem of oxidation of the battery diaphragm, and the polyethylene on the other side provides better transverse tensile strength to improve the mechanical properties of the composite diaphragm.
[0041] According to the embodiments of the present application, referring to Figure 4 The composite aluminum oxide layer 10 is located on opposite sides of the polymer layer 20. In this way, the temperature resistance, high-temperature dimensional stability and thermal conductivity of the composite separator can be further improved, the effect of the edge curling of the separator is further improved, and the safety performance of the battery using the composite separator can be further improved.
[0042] According to the embodiments of the present application, referring to Figure 5 The composite aluminum oxide layer includes pores, the pores include large pores 101 and small pores 102, the small pores 102 are located in the porous aluminum oxide layer 12, the large pores 101 penetrate through the intermediate aluminum foil or penetrate through the porous aluminum oxide layer 12 on one side of the intermediate aluminum foil and extend into the intermediate aluminum foil 11, and the diameter φ1 of the large pores and the diameter φ2 of the small pores satisfy: φ2 < φ1. In this way, by designing the small pores combined with the large pores, the straight-through holes can be avoided, the tortuosity of lithium ion transmission is increased, which is helpful to inhibit the growth of lithium dendrites and further improve the safety of the battery.
[0043] According to the embodiments of the present application, the diameter φ1 of the large pores is 5 μm to 50 μm, and specifically, φ1 can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or any range between any two of them. In this way, the diameter of the large pores is moderate, which is helpful to improve the uniformity of the large pores. If the diameter is too large, the uniformity is not good and may be locally concentrated, and if the diameter is too small, the preparation difficulty is increased.
[0044] According to the embodiments of the present application, the diameter φ2 of the small pores is 20 nm to 5 μm; specifically, φ2 can be 20 nm, 100 nm, 500 nm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any range between any two of them. In this way, the diameter of the small pores is moderate, which is helpful to improve the uniformity of the small pores. If the diameter is too large, the uniformity is not good and may be locally concentrated, and if the diameter is too small, the preparation difficulty is increased.
[0045] In this article, the diameter of the large pores and the small pores refers to the longest distance between any two points on the pore wall in the same horizontal plane, which can be detected by the SEM method.
[0046] According to embodiments of the present application, the gap I1 between two adjacent large holes is 5-50 μm, specifically, I1 can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or any range between any two of them. Thus, the large holes have a suitable density, so that the composite alumina layer has a suitable porosity, which can ensure the transmission of active ions, while having a high tortuosity, if the gap is too large, the mechanical strength of the composite separator can be low, if the gap is too small, the active ion transmission impedance can be high.
[0047] According to embodiments of the present application, the gap I2 between two adjacent small holes is 30 nm-1 μm; specifically, I2 can be 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm or any range between any two of them. Thus, the small holes have a suitable density, so that the composite alumina layer has a suitable porosity, which can ensure the transmission of active ions, while having a high tortuosity, if the gap is too large, the mechanical strength of the composite separator can be low, if the gap is too small, the active ion transmission impedance can be high.
[0048] Herein, the gap between two adjacent large holes and the gap between two adjacent small holes refer to the distance between the geometric centers of the two adjacent holes, which can be detected by SEM method.
[0049] According to embodiments of the present application, the coverage L1 of the large holes is 5%-50%; specifically, L1 can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any range between any two of them. Thus, the large holes have a suitable density, so that the composite alumina layer has a suitable porosity, which can ensure the transmission of active ions, while having a high tortuosity, if the coverage is too large, the mechanical strength of the composite separator can be low, if the coverage is too small, the active ion transmission impedance can be high.
[0050] According to embodiments of the present application, the coverage L2 of the small holes is 5%-60%; specifically, L2 can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any range between any two of them. Thus, the small holes have a suitable density, so that the composite alumina layer has a suitable porosity, which can ensure the transmission of active ions, while having a high tortuosity, if the coverage is too large, the mechanical strength of the composite separator can be low, if the coverage is too small, the active ion transmission impedance can be high.
[0051] Herein, the coverage of the large pores and the small pores refers to the proportion of the area of the pores to the area of the whole surface (the surface of the porous alumina layer away from the central aluminum foil), which can be detected by the SEM method. It can be understood that the sum of the coverage of the large pores and the small pores is less than or equal to 100%.
[0052] According to the embodiments of the present application, the depth H1 of the large pores is the sum of the thickness of the intermediate aluminum foil 11 and the single-sided porous alumina layer 12 or the thickness of the intermediate aluminum foil 11. That is, the large pores can form through holes only through the intermediate aluminum foil, or can simultaneously pass through the single-layer porous alumina layer and the intermediate aluminum foil. Thus, a transmission channel for active ions can be provided. In some embodiments, H1 can be specifically 0.5 μm to 5 μm, specifically, 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm or a range between any two of them. Thus, the active ions can smoothly pass through the composite separator, and have a high tortuosity, both have a low impedance, and can effectively improve the lithium dendrite problem.
[0053] According to the embodiments of the present application, the depth H2 of the small pores is the thickness of the single-sided porous alumina layer 12. Thus, a transmission channel for active ions can be provided. In some embodiments, H2 can be specifically 0.2 μm to 5 μm, specifically, 0.2 μm, 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm or a range between any two of them. Thus, the active ions can smoothly pass through the composite separator, and have a high tortuosity, both have a low impedance, and can effectively improve the lithium dendrite problem.
[0054] Herein, the depth of the large pores and the small pores refers to the size of the pores along the thickness direction (i.e. the stacking direction of the intermediate aluminum foil and the porous alumina layer), which can be detected by the SEM method.
[0055] According to the embodiments of the present application, in order to further improve the performance of the composite separator, the pores in the porous alumina layer in the composite alumina layer can be further provided with a functional material, which includes at least one of a solid-state electrolyte, a lithium supplement material, an organic polymer and a binder. Thus, the electrolyte wetting performance of the composite separator can be further improved, and then the problem of uneven distribution of the electrolyte can be improved, so that the local lithium precipitation of the battery is improved; the lithium supplement effect can also be achieved to reduce the capacity attenuation of the battery and prolong the cycle life of the battery; the organic polymer can be melted when the temperature rises to the melting point of the organic polymer, the pores are sealed, the thermal shutdown is realized, and the safety of the battery is provided; and the binder penetrates into the pores, which can realize the advantages of enhanced bonding force without increasing the thickness of the separator.
[0056] According to an embodiment of the present application, the solid-state electrolyte comprises lithium aluminum titanium phosphate. In this way, the effect of improving the electrolyte wetting performance of the composite separator is further improved, and in turn the problem of uneven distribution of electrolyte and local lithium precipitation in the battery can be further improved.
[0057] According to an embodiment of the present application, the lithium supplementing material comprises at least one of Li6CoO4, Li5FeO4, Li2C2O4, Li2NiO2. In this way, the composite separator can also have a lithium supplementing effect, reducing the loss of active ions in the battery, thereby reducing the capacity decay of the battery and prolonging the cycle life of the battery.
[0058] According to an embodiment of the present application, the organic polymer comprises at least one of polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA). In this way, when the temperature rises to the melting point of the organic polymer, the material melts, the pores are sealed, and thermal shutdown is achieved, providing battery safety.
[0059] According to an embodiment of the present application, the binder comprises a particulate binder. In this way, the advantage of enhanced bonding force without increasing the thickness of the separator can be achieved.
[0060] According to an embodiment of the present application, the thickness of the composite separator is 3 μm to 20 μm, specifically 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or any range between any two of them. Within this thickness range, the mechanical properties meet the requirements while meeting the insulation performance, and the mass is lighter, which is beneficial to improving the overall performance of the battery.
[0061] According to an embodiment of the present application, the thickness of the polymer layer is 2 μm to 22 μm, specifically 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm or any range between any two of them. In this way, the composite separator has good toughness at low temperature, and can quickly melt and seal the pores at high temperature to achieve thermal shutdown and improve the safety of the battery.
[0062] According to an embodiment of the present application, the porosity of the polymer layer is 20% to 70%, specifically 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or any range between any two of them. In this way, the active ions can be smoothly transmitted through the composite separator, and at the same time have better mechanical properties. If the porosity is too small, the impedance of active ion transmission may be high, and if the porosity is too large, the mechanical strength of the composite separator may be reduced, and the probability of short circuit may be increased.
[0063] According to embodiments of the present application, the intermediate aluminum foil has a thickness of 0.5 μm to 3 μm, specifically 0.5 μm, 1 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3 μm or a range between any two of them. In this way, the excellent thermal conductivity can further improve the safety of the battery.
[0064] According to embodiments of the present application, the porous aluminum oxide layer has a thickness of 0.3 μm to 2.5 μm, specifically 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 2.0 μm, 2.5 μm or a range between any two of them. In this way, the better skeleton support effect, the better temperature resistance and high-temperature dimensional stability, and the further improved effect of improving the safety of the battery are achieved.
[0065] In a second aspect, the present application provides a method for preparing the composite separator described above. According to embodiments of the present application, the method comprises: taking an aluminum foil as an anode, anodizing at least one side surface of the aluminum foil to form an oxide layer on the at least one side surface of the aluminum foil, and obtaining an anodized product; and performing a pore-forming treatment on the anodized product to obtain a composite aluminum oxide layer. Specifically, by anodizing, a porous aluminum oxide layer with small pores can be formed on at least one side surface of the aluminum foil, and by further pore-forming treatment, large pores can be formed. In this way, by combining the large pores and the small pores, a transmission channel for active ions can be formed in the composite aluminum oxide layer, and part of the aluminum foil is still not oxidized to form an intermediate aluminum foil. Therefore, the method is simple to operate, and the composite separator obtained by the method has better temperature resistance and high-temperature dimensional stability, and the battery using the composite separator has higher safety.
[0066] It can be understood that the anodizing treatment can be performed according to the following steps: taking an aluminum foil as an anode, additionally providing a cathode, placing the anode and the cathode in an electrolyte, and connecting a power source between the anode and the cathode. Under the action of the electric field, the aluminum foil as the anode is oxidized to form a porous aluminum oxide layer.
[0067] According to embodiments of the present application, the electrolytic solution for anodizing can comprise at least one of oxalic acid, phosphoric acid and sulfuric acid. In this way, the electrolyte is conducive to forming a porous aluminum oxide layer with appropriate thickness, high density and high mechanical strength.
[0068] According to embodiments of the present application, the cathode for anodizing comprises a platinum electrode. In this way, the platinum electrode is stable in nature, does not dissolve any metal ions, has uniform current distribution, is resistant to corrosion, has a long service life, has a low overpotential, and has a better anodizing effect.
[0069] According to embodiments of the present application, the current density for anodizing is 1 A / dm 2 ~5 A / dm 2 , specifically 1 A / dm2 1.5 A / dm 2 2 A / dm 2 2.5 A / dm 2 3 A / dm 2 3.5 A / dm 2 4 A / dm 2 4.5 A / dm 2 5 A / dm 2 or any range between any two of them. In the above current density range, a porous alumina layer with appropriate thickness and high mechanical strength can be generated at a faster speed.
[0070] According to embodiments of the present application, the temperature of the anodization is 0℃-60℃, specifically 0℃, 5℃, 10℃, 15℃, 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, 60℃ or any range between any two of them. In the above temperature range, the film formation rate is faster, the tact time is shortened, the cell voltage is lower, thereby reducing the energy consumption, and meanwhile the current efficiency is high, which is conducive to obtaining appropriate small pores.
[0071] According to embodiments of the present application, the time of the anodization is 10 min-10 h, specifically 10 min, 30 min, 45 min, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any range between any two of them. In the above time range, a porous alumina layer with appropriate thickness can be obtained, and the corrosion resistance, wear resistance and insulation performance of the obtained porous alumina layer are effectively improved.
[0072] According to embodiments of the present application, the pore-forming treatment includes at least one of chemical etching, focused ion beam etching and laser drilling. In this way, a macropore with appropriate aperture and depth can be conveniently and quickly prepared, and a better transmission channel is provided for active ions.
[0073] According to embodiments of the present application, the chemical etching can corrode the target substance by an acid solution or an alkali solution, so as to form a macropore structure in the composite alumina layer. The specific chemical etching solution can be selected according to the target macropore, which is not particularly limited in the present application.
[0074] According to embodiments of the present application, the ion beam current used in the focused ion beam etching is 1 pA-50 pA; specifically 1 pA, 5 pA, 10 pA, 15 pA, 20 pA, 25 pA, 30 pA, 35 pA, 40 pA, 45 pA, 50 pA or any range between any two of them. In the above current range, the material removal rate is higher, the processing efficiency is higher, and a macropore with larger diameter and greater depth can be formed at one time, and meanwhile the processing precision is higher.
[0075] According to embodiments of the present application, the residence time of the focused ion beam etching is 50 μs to 1000 μs; specifically, 50 μs, 100 μs, 200 μs, 300 μs, 400 μs, 500 μs, 600 μs, 700 μs, 800 μs, 900 μs, 1000 μs, or a range between any two of them. Within the above time range, the etching precision and edge steepness are improved, and the heat accumulation and ion damage are reduced, while the aspect ratio capability is improved.
[0076] According to embodiments of the present application, the laser frequency used in the laser drilling is 100 Hz to 1000 Hz; specifically, 100 Hz, 200 Hz, 300 Hz, 400 Hz, 500 Hz, 600 Hz, 700 Hz, 800 Hz, 900 Hz, 1000 Hz, or a range between any two of them.
[0077] According to embodiments of the present application, the drilling speed of the laser drilling is 0.5 m / min to 5 m / min; specifically, 0.5 m / min, 1 m / min, 1.5 m / min, 2 m / min, 2.5 m / min, 3 m / min, 3.5 m / min, 4 m / min, 4.5 m / min, 5 m / min, or a range between any two of them. Within the above range, the processing efficiency is higher, the hole wall is smoother, the heat accumulation effect is lower, and the slag, edge collapse or carbonization phenomenon is less likely to occur, and a large hole with high aspect ratio is obtained.
[0078] According to embodiments of the present application, the functional material can also be in the voids of the porous alumina layer, and therefore the method for preparing the composite separator can further comprise: depositing a functional material into the pores of the composite alumina layer.
[0079] According to embodiments of the present application, the deposition method comprises chemical vapor deposition. In this way, the functional material can be effectively deposited into the pores, and the method is mature.
[0080] According to embodiments of the present application, the composite separator can further comprise a polymer layer, and therefore the method for preparing the composite separator can further comprise: compounding the composite alumina layer and the polymer layer.
[0081] According to embodiments of the present application, the compounding comprises: stacking the composite alumina layer and the polymer layer, and pressing the obtained stack product to make them compound. In this way, the composite alumina layer and the polymer layer can be compounded conveniently and quickly, and the bonding strength between them in the obtained composite separator is higher.
[0082] The method for preparing the composite separator according to the present application is described in detail below, taking the composite separator comprising the composite alumina layer and the polymer layer on both sides of the composite alumina layer as an example. Oxalic acid, phosphoric acid, sulfuric acid, etc. are used as acidic electrolytic solution, aluminum foil is used as anode, platinum electrode is used as cathode, and the current density is 1~5A / dm 2 , under the condition of temperature of 0~60℃, anodize for 10min~10h. After turning the aluminum foil over, repeat the above operation to obtain a double-sided aluminum oxide layer. The anodized aluminum foil is subjected to a pore-forming treatment, wherein the ion beam current used in focused ion beam etching is 1~50pA, the dwell time is 50~1000μs, and the laser drilling uses a laser with a laser frequency of 100~1000Hz, the drilling speed is 0.5~5m / min, and the pore diameter can be 10 nm~100μm. After turning the foil over, repeat the above pore-forming treatment operation. The polyethylene membrane, porous alumina layer, and polypropylene membrane sandwich structure are stacked and then compounded under a pressure of 4.0Mpa to obtain the above-mentioned three-layer composite high-safety composite membrane.
[0083] In a third aspect, the present application provides a battery. According to an embodiment of the present application, the battery includes the aforementioned composite diaphragm or a composite diaphragm prepared by the aforementioned method. The battery significantly reduces the probability of short circuits and thermal runaway, thereby providing high safety.
[0084] According to the embodiments of the present application, it can be understood that the specific type of the battery is not particularly limited and can be a primary battery or a secondary battery; the shape of the battery can be a cylindrical battery, a square battery, or a battery of any other shape, and according to the outer packaging, the battery can be a hard-shell battery, a soft-pack battery, etc. In other embodiments, the battery can be a lithium-ion battery, a sodium-ion battery, etc.
[0085] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and the aforementioned composite separator. The positive electrode sheet, the negative electrode sheet, and the composite separator can be made into a battery cell through a winding or lamination process, and the battery cell and the electrolyte can be contained in an outer package. During the battery's charge and discharge process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte acts as an ion conductor between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0086] The positive electrode sheet in the battery may include a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer is arranged on at least one surface of the positive electrode current collector.
[0087] In some embodiments, the positive electrode current collector can be a metal current collector or a composite current collector. For example, the metal current collector can include, but is not limited to, an aluminum foil current collector; the composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer material base layer (such as a base layer of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0088] In some embodiments, the positive electrode active material layer can include a positive electrode active material, a binder, and a conductive agent, and additives with specific functions and effects can also be added according to actual needs, such as thickening agents, sodium supplementing agents, film-forming additives, flame retardants, high / low temperature stabilizers, etc.
[0089] As an example, the positive electrode active material of the battery can include lithium nickel cobalt manganese oxide (including but not limited to NCM811, NCM613, NCM523, etc.), lithium cobaltate, lithium iron phosphate, lithium manganese iron phosphate, lithium manganate, lithium nickel manganate, lithium-rich manganese-based material, or a positive electrode active material commonly used in the art.
[0090] As an example, the binder in the positive electrode active material layer can include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylic ester-based resin.
[0091] As an example, the conductive agent in the positive electrode active material layer can include at least one of super-conductive carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0092] In some embodiments, the negative electrode sheet can include a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector.
[0093] As an example, the negative electrode active material layer can include a negative electrode active material, a thickening agent, a conductive agent, and a binder, wherein the negative electrode current collector can be a metal foil, for example, the metal foil can be a copper foil.
[0094] According to embodiments of the present application, the negative electrode active material can include a carbon-based material, a silicon-based material, a tin-based material, etc.
[0095] According to embodiments of the present application, the binder in the negative material layer can include, but is not limited to, at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0096] According to embodiments of the present application, the conductive agent in the negative material layer can include, but is not limited to, at least one of super conductive carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0097] In a fourth aspect, the present application provides a battery pack. According to embodiments of the present application, the battery pack includes the composite separator described above, the composite separator prepared by the method described above, or the battery described above. The battery pack has better safety performance.
[0098] It can be understood that the battery pack can be a battery module, a battery pack, or the like. Specifically, the specific structure of the battery module and the battery pack can refer to the conventional techniques in the art, which will not be described herein.
[0099] In a fifth aspect, the present application provides a power consuming device. According to embodiments of the present application, the power consuming device includes the composite separator described above, the composite separator prepared by the method described above, the battery described above, or the battery pack described above. The power consuming device has all the features and advantages of the battery described above or the battery pack described above, which will not be described herein.
[0100] According to embodiments of the present application, the specific type of the power consuming device is not particularly limited, and can be any device that uses a battery as a power source or an energy storage unit. As an example, the power consuming device includes, but is not limited to, an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a mobile terminal (such as a mobile phone, a notebook computer, a game console, a wearable device, etc.), a drone, an aerospace device, a satellite, a ship, an energy storage system, and the like.
[0101] It can be understood that, in addition to the battery described above, the power consuming device also includes necessary structures and components, which can refer to conventional techniques, for example, an electric vehicle can include a vehicle body, a chassis, tires, a navigation system, a radar system, a steering system, a braking system, a lubrication system, a cooling system, a driving system, and the like, which will not be described herein.
[0102] Embodiments of the present application will be described in detail below.
[0103] Example 1 Anodization: 3.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under the conditions of a current density of 3 A / dm2, a temperature of 25°C, and an anodization time of 1 h. After the aluminum foil was turned over, the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both sides of the intermediate aluminum foil. 2 2 Anodization: 3.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under the conditions of a current density of 3 A / dm2, a temperature of 25°C, and an anodization time of 1 h. After the aluminum foil was turned over, the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both sides of the intermediate aluminum foil.
[0104] Pore formation: The anodization product was subjected to pore formation, which can include focused ion beam etching followed by laser drilling, wherein the focused ion beam etching uses an ion beam current of 25 pA and a dwell time of 400 ps, and the laser drilling uses a laser frequency of 400 Hz and a drilling speed of 1 m / min. After the foil was turned over, the above drilling operation was repeated to obtain a composite aluminum oxide layer.
[0105] A three-layer composite separator was obtained by drying after bonding and molding of polyethylene having a thickness of 3 pm and a porosity of 30%, the above composite aluminum oxide layer, and polypropylene having a thickness of 3 pm and a porosity of 30% at 25°C and 4 MPa.
[0106] In the porous aluminum oxide layer, the diameter of the large pores is 20 pm, the diameter of the small pores is 50 nm, the depth of the large pores is 3 pm, the depth of the small pores is 0.5 pm, the gap between adjacent large pores is 20 pm, the gap between adjacent small pores is 30 nm, the coverage of the large pores is 19.63%, and the coverage of the small pores is 30.68%.
[0107] Example 2 Anodization: 3.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under the conditions of a current density of 3 A / dm2, a temperature of 25°C, and an anodization time of 1 h. After the aluminum foil was turned over, the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both sides of the intermediate aluminum foil.
[0108] Pore formation: The anodization product was subjected to pore formation, which can include focused ion beam etching followed by laser drilling, wherein the focused ion beam etching uses an ion beam current of 25 pA and a dwell time of 400 ps, and the laser drilling uses a laser frequency of 400 Hz and a drilling speed of 1 m / min. After the foil was turned over, the above drilling operation was repeated to obtain a composite aluminum oxide layer.
[0109] The three-layer composite separator was obtained by drying after laminating and molding of polyethylene with a thickness of 3 μm and a porosity of 30%, the composite alumina layer, and polypropylene with a thickness of 3 μm and a porosity of 30% at 25°C and 4 MPa.
[0110] In the porous alumina layer, the diameter φ1 of the large pores is 5 μm, the diameter φ2 of the small pores is 50 nm, the depth H1 of the large pores is 1 μm, the depth H2 of the small pores is 0.5 μm, the gap I1 between adjacent two large pores is 5 μm, the gap I2 between adjacent two small pores is 30 nm, the coverage L1 of the large pores is 19.63%, and the coverage L2 of the small pores is 30.68%.
[0111] Example 3 Anodic oxidation treatment: 5.5 μm aluminum foil was oxidized and etched, an acidic electrolytic solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water was used, the aluminum foil was used as an anode, and a platinum electrode was used as a cathode, and the anodic oxidation treatment was performed at a current density of 3 A / dm 2 2, a temperature of 25°C, and a treatment time of 1 h. After the aluminum foil was turned over, the above anodic oxidation operation was repeated to form a porous alumina layer with small pores, thereby obtaining an anodic oxidation product having an intermediate aluminum foil and a porous alumina layer on both surfaces of the intermediate aluminum foil.
[0112] Pore forming treatment: the anodic oxidation product was subjected to pore forming treatment, and the pore forming treatment conditions can include: first, focused ion beam etching, and then laser punching, wherein the ion beam current of the focused ion beam etching is 50 pA, and the residence time is 800 μs, and the laser punching uses a laser frequency of 200 Hz and a punching speed of 2 m / min. After the foil was turned over, the above punching operation was repeated to obtain a composite alumina layer.
[0113] The three-layer composite separator was obtained by drying after laminating and molding of polyethylene with a thickness of 3 μm and a porosity of 30%, the composite alumina layer, and polypropylene with a thickness of 3 μm and a porosity of 30% at 25°C and 4 MPa.
[0114] In the porous alumina layer, the diameter φ1 of the large pores is 5 μm, the diameter φ2 of the small pores is 50 nm, the depth H1 of the large pores is 1 μm, the depth H2 of the small pores is 0.5 μm, the gap I1 between adjacent two large pores is 5 μm, the gap I2 between adjacent two small pores is 30 nm, the coverage L1 of the large pores is 19.63%, and the coverage L2 of the small pores is 30.68%.
[0115] Example 4 Anodization: 3.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under conditions of a current density of 2 A / dm2, a temperature of 35°C, and an anodization time of 1 h. The aluminum foil was flipped over and the above anodization operation was repeated to form a porous aluminum oxide layer having large pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both surfaces of the intermediate aluminum foil. 2 2 Anodization: 5.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under conditions of a current density of 5 A / dm2, a temperature of 35°C, and an anodization time of 3 h. The aluminum foil was flipped over and the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both surfaces of the intermediate aluminum foil.
[0116] Pore formation: The anodization product was subjected to pore formation, which can include focused ion beam etching followed by laser drilling, wherein the focused ion beam etching uses an ion beam current of 25 pA and a dwell time of 400 ps, and the laser drilling uses a laser frequency of 400 Hz and a drilling speed of 1 m / min. The foil was flipped over and the above drilling operation was repeated to obtain a composite aluminum oxide layer.
[0117] A three-layer composite separator was obtained by drying after bonding and molding of a 3 pm-thick polyethylene having a porosity of 30%, the above composite aluminum oxide layer, and a 3 pm-thick polypropylene having a porosity of 30% at 25°C and 4 MPa.
[0118] In the porous aluminum oxide layer, the diameter of the large pores is 20 pm, the diameter of the small pores is 20 nm, the depth of the large pores is 3 pm, the depth of the small pores is 0.5 pm, the gap between adjacent large pores is 20 pm, the gap between adjacent small pores is 20 nm, the coverage of the large pores is 19.63%, and the coverage of the small pores is 19.63%.
[0119] Example 5 Anodization: 5.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under conditions of a current density of 5 A / dm2, a temperature of 35°C, and an anodization time of 3 h. The aluminum foil was flipped over and the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both surfaces of the intermediate aluminum foil.
[0120] Pore formation: The anodization product was subjected to pore formation, which can include focused ion beam etching followed by laser drilling, wherein the focused ion beam etching uses an ion beam current of 25 pA and a dwell time of 400 ps, and the laser drilling uses a laser frequency of 400 Hz and a drilling speed of 1 m / min. The foil was flipped over and the above drilling operation was repeated to obtain a composite aluminum oxide layer.
[0121] A three-layer composite separator was obtained by drying after laminating and molding at 25°C, 4MPa, a 3μm-thick, 30% porosity polyethylene, the composite alumina layer, and a 3μm-thick, 30% porosity polypropylene.
[0122] In the porous alumina layer, the diameter φ1 of the large pores is 20μm, the diameter φ2 of the small pores is 5μm, the depth H1 of the large pores is 3μm, the depth H2 of the small pores is 2.5μm, the gap I1 between adjacent large pores is 20μm, the gap I2 between adjacent small pores is 1μm, the coverage L1 of the large pores is 19.63%, and the coverage L2 of the small pores is 54.54%.
[0123] Example 6 Anodization: A 4μm aluminum foil was anodized and etched using a solution comprising 5wt% oxalic acid, 2wt% phosphoric acid, 1wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode at a current density of 1A / dm 2 2 at a temperature of 45°C for 1h. After turning over the aluminum foil, the above anodization operation was repeated to form a porous alumina layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous alumina layer on both surfaces of the intermediate aluminum foil.
[0124] Pore formation: The anodization product was subjected to pore formation, which can include focused ion beam etching followed by laser drilling, wherein the focused ion beam etching uses an ion beam current of 25pA and a residence time of 400μs, and the laser drilling uses a laser frequency of 400Hz and a drilling speed of 1m / min. After turning over the foil, the above drilling operation was repeated to obtain a composite alumina layer.
[0125] A 1% concentration PVDF binder solution was transferred to both surfaces of the composite alumina layer using gravure coating, then a 3μm-thick, 30% porosity polypropylene separator was placed on one side, and a 3μm-thick, 30% porosity polyethylene separator was placed on the other side, and after laminating and molding at 25°C, 0.3MPa for 1s, drying was performed to obtain a three-layer composite separator.
[0126] In the porous alumina layer, the diameter φ1 of the large pores is 20μm, the diameter φ2 of the small pores is 70μm, the depth H1 of the large pores is 3.5μm, the depth H2 of the small pores is 0.5μm, the gap I1 between adjacent large pores is 20μm, the gap I2 between adjacent small pores is 25μm, the coverage L1 of the large pores is 19.63%, and the coverage L2 of the small pores is 35%.
[0127] Example 7 Anodization: 3.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under the condition of a current density of 3 A / dm2, a temperature of 25 °C, and anodization for 1 h. After the aluminum foil was turned over, the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both sides of the intermediate aluminum foil. 2 Anodization: 3.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under the condition of a current density of 3 A / dm2, a temperature of 25 °C, and anodization for 1 h. After the aluminum foil was turned over, the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both sides of the intermediate aluminum foil.
[0128] Pore formation: The anodization product was subjected to pore formation, which can include focused ion beam etching followed by laser drilling, wherein the focused ion beam etching uses an ion beam current of 25 pA and a dwell time of 400 ps, and the laser drilling uses a laser frequency of 400 Hz and a drilling speed of 1 m / min. After the foil was turned over, the above drilling operation was repeated to obtain a composite aluminum oxide layer.
[0129] In the porous aluminum oxide layer, the diameter of the large pores is 20 pm, the diameter of the small pores is 50 nm, the depth of the large pores is 3 pm, the depth of the small pores is 0.5 pm, the gap between adjacent two large pores is 20 pm, the gap between adjacent two small pores is 30 nm, the coverage of the large pores is 19.63%, and the coverage of the small pores is 30.68%.
[0130] Example 8 Anodization: 3.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under the condition of a current density of 3 A / dm2, a temperature of 25 °C, and anodization for 1 h. After the aluminum foil was turned over, the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both sides of the intermediate aluminum foil. 2 Anodization: 3.5 pm aluminum foil was anodized and etched using a solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water as an acidic electrolytic solution, the aluminum foil as an anode, and a platinum electrode as a cathode, under the condition of a current density of 3 A / dm2, a temperature of 25 °C, and anodization for 1 h. After the aluminum foil was turned over, the above anodization operation was repeated to form a porous aluminum oxide layer having small pores, thereby obtaining an anodization product having an intermediate aluminum foil and a porous aluminum oxide layer on both sides of the intermediate aluminum foil.
[0131] Pore formation: The anodization product was subjected to pore formation, which can include focused ion beam etching followed by laser drilling, wherein the focused ion beam etching uses an ion beam current of 25 pA and a dwell time of 400 ps, and the laser drilling uses a laser frequency of 400 Hz and a drilling speed of 1 m / min. After the foil was turned over, the above drilling operation was repeated to obtain a composite aluminum oxide layer.
[0132] 1% concentration of PVDF binder solution is transferred to one surface of the composite alumina layer by gravure coating method, and then a polyethylene separator with a thickness of 3 μm and a porosity of 30% is placed on the adhesive side to form a composite separator after drying at 25°C and 0.3 MPa for 1 s.
[0133] In the porous alumina layer, the diameter φ1 of the large pores is 20 μm, the diameter φ2 of the small pores is 50 nm, the depth H1 of the large pores is 3 μm, the depth H2 of the small pores is 0.5 μm, the gap I1 between adjacent two large pores is 20 μm, the gap I2 between adjacent two small pores is 30 nm, the coverage L1 of the large pores is 19.63%, and the coverage L2 of the small pores is 30.68%.
[0134] Example 9 Anodic oxidation treatment: 3.5 μm aluminum foil is oxidized and etched, an acidic electrolytic solution including 5 wt% oxalic acid, 2 wt% phosphoric acid, 1 wt% sulfuric acid, and the balance water is used as the acid electrolytic solution, the aluminum foil is used as the anode, and a platinum electrode is used as the cathode, and the anodic oxidation treatment is performed at a current density of 3 A / dm 2 2 at a temperature of 25°C for 1 h. After the aluminum foil is turned over, the above anodic oxidation operation is repeated to form a porous alumina layer with small pores, thereby obtaining an anodic oxidation product having an intermediate aluminum foil and a porous alumina layer on both surfaces of the intermediate aluminum foil.
[0135] Pore forming treatment: the anodic oxidation product is subjected to pore forming treatment, which can include the following conditions: first, focused ion beam etching is performed, and then laser drilling is performed, wherein the ion beam current of the focused ion beam etching is 25 pA, and the residence time is 400 μs, and the laser drilling uses a laser frequency of 400 Hz and a drilling speed of 1 m / min. After the foil is turned over, the above drilling operation is repeated to obtain a composite alumina layer.
[0136] A 1% concentration of PVDF binder solution is transferred to both surfaces of the composite alumina layer by gravure coating method, and a polyethylene separator with a thickness of 3 μm and a porosity of 30% is placed on each adhesive surface to form a three-layer composite separator after drying at 25°C and 0.3 MPa for 1 s.
[0137] Example 10 The separator is prepared according to the preparation method of Example 1, and the difference between this example and Example 1 is that the residence time of the focused ion beam etching is 100 μs, and the aluminum foil is subjected to anodic oxidation treatment on one side for 6 h, thereby obtaining a composite separator composed of a composite alumina layer, and only the intermediate aluminum foil has a porous alumina layer on one side, and the pore forming treatment is performed on the side that has not been subjected to anodic oxidation, and the formed large pores only penetrate the intermediate aluminum foil.
[0138] The diameter φ1 of the large holes in the porous aluminum oxide layer is 20 μm, the diameter φ2 of the small holes is 50 nm, the depth H1 of the large holes is 0.5 μm (i.e. the thickness of the middle aluminum foil), the depth H2 of the small holes is 3 μm, the gap I1 between adjacent two large holes is 20 μm, the gap I2 between adjacent two small holes is 30 nm, the coverage L1 of the large holes is 19.63%, and the coverage L2 of the small holes is 30.68%.
[0139] Example 11 The separator is prepared according to the preparation method of Example 1, except that the focused ion beam etching residence time is 500 μs, and the anodization treatment time is 10 min.
[0140] The diameter φ1 of the large holes in the porous aluminum oxide layer is 20 μm, the diameter φ2 of the small holes is 50 nm, the depth H1 of the large holes is 3.3 μm, the depth H2 of the small holes is 0.2 μm, the gap I1 between adjacent two large holes is 20 μm, the gap I2 between adjacent two small holes is 30 nm, the coverage L1 of the large holes is 19.63%, and the coverage L2 of the small holes is 30.68%.
[0141] Example 12 The separator is prepared according to the preparation method of Example 1, except that the laser drilling frequency is 400 Hz, and the drilling speed is 0.25 m / min.
[0142] The diameter φ1 of the large holes in the porous aluminum oxide layer is 20 μm, the diameter φ2 of the small holes is 50 nm, the depth H1 of the large holes is 3.3 μm, the depth H2 of the small holes is 0.2 μm, the gap I1 between adjacent two large holes is 20 μm, the gap I2 between adjacent two small holes is 30 nm, the coverage L1 of the large holes is 5%, and the coverage L2 of the small holes is 30.68%.
[0143] Example 13 The separator is prepared according to the preparation method of Example 1, except that the laser drilling frequency is 400 Hz, and the drilling speed is 2.5 m / min.
[0144] The diameter φ1 of the large holes in the porous aluminum oxide layer is 20 μm, the diameter φ2 of the small holes is 50 nm, the depth H1 of the large holes is 3.3 μm, the depth H2 of the small holes is 0.2 μm, the gap I1 between adjacent two large holes is 20 μm, the gap I2 between adjacent two small holes is 30 nm, the coverage L1 of the large holes is 50%, and the coverage L2 of the small holes is 30.68%.
[0145] Example 14 A separator was prepared according to the preparation method of Example 1, except that a solution comprising 0.5 wt% oxalic acid, 0.5 wt% phosphoric acid, 0.2 wt% sulfuric acid, and the balance water was used as the acidic electrolytic solution and the anodization was performed at a current density of 1 A / dm 2 at 25°C for 1 h.
[0146] wherein the diameter φ1 of the large pores in the porous alumina layer is 20 μm, the diameter φ2 of the small pores is 50 nm, the depth H1 of the large pores is 3.3 μm, the depth H2 of the small pores is 0.2 μm, the gap I1 between adjacent two large pores is 20 μm, the gap I2 between adjacent two small pores is 30 nm, the coverage L1 of the large pores is 19.63%, and the coverage L2 of the small pores is 5%.
[0147] Example 15 A separator was prepared according to the preparation method of Example 1, except that a solution comprising 4 wt% oxalic acid, 4 wt% phosphoric acid, 2 wt% sulfuric acid, and the balance water was used as the acidic electrolytic solution and the anodization was performed at a current density of 1 A / dm 2 at 25°C for 1 h.
[0148] wherein the diameter φ1 of the large pores in the porous alumina layer is 20 μm, the diameter φ2 of the small pores is 50 nm, the depth H1 of the large pores is 3.3 μm, the depth H2 of the small pores is 0.2 μm, the gap I1 between adjacent two large pores is 20 μm, the gap I2 between adjacent two small pores is 30 nm, the coverage L1 of the large pores is 19.63%, and the coverage L2 of the small pores is 60%.
[0149] Example 16 The same as Example 1, except that the composite separator comprises a polyethylene film and a composite alumina layer on both sides of the polyethylene film.
[0150] Comparative Example 1 A two-layer composite separator was obtained by drying a polyethylene film having a thickness of 3 μm and a porosity of 30% and a polypropylene film having a thickness of 3 μm and a porosity of 30% after being laminated at 25°C and 4 MPa.
[0151] An alumina slurry formulation: alumina: 55 parts by weight; water: 55 parts by weight; binder: butyl acrylate 10 parts by weight; CMC: 1 part by weight; polyether silicone: 2 parts by weight, was coated on one side of the polyethylene separator using a gravure, with a coating thickness of 3 μm, and a coated separator was obtained after drying.
[0152] Performance test: 1. Thermal shrinkage: (1) Use a cutter to cut a 150mm x 100mm square sample from the composite separator roll; (2) Measure the horizontal and vertical dimensions of the composite separator using a projector and record the data; (3) Place the completed test composite separator sample flat in an A4 book; (4) Place the A4 book with the composite separator sample in an oven set to 1h at 95°C; (5) After the baking time is over, measure the horizontal and vertical dimensions of the composite separator at the same location using a projector; (6) Record the data and calculate the heat shrinkage rate of the separator, heat shrinkage rate = (original width - width after baking) / original width.
[0153] 2. Hot puncture strength: tested using a puncture strength tester, with a temperature setting of 80°C, and the test method referring to GB / T36294-2018.
[0154] 3. Ionic conductivity: composite separator ionic conductivity was measured according to BG / T 36294-2018.
[0155] 4. Battery thermal runaway temperature: Battery assembly: 1) Preparation of positive electrode sheet After the positive electrode active material lithium iron phosphate, conductive agent conductive carbon black, binder PVDF, solvent NMP were stirred and mixed uniformly according to a mass ratio of 100:8:2.5:60, a positive electrode slurry was obtained, the positive electrode slurry was coated on both sides of the surface of the positive electrode current collector aluminum foil, and the positive electrode sheet was obtained after drying, rolling, and sheeting.
[0156] 2) Preparation of negative electrode sheet After the negative electrode active material graphite, SBR, CMC, conductive graphite, NMP and H2O were stirred and mixed according to a mass ratio of 100:3:1.5:1:2:115, a negative electrode slurry was obtained, the negative electrode slurry was coated on both sides of the surface of the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, rolling, and sheeting.
[0157] 3) Preparation of electrolyte Electrolyte (the electrolyte is composed of 13wt% LiPF6, 26wt% EC, and 61wt% DEC) 4) Preparation of lithium ion battery After the above-prepared negative electrode sheet, the separator of each example or comparative example, and the positive electrode sheet were placed in order, a cell was obtained by winding, the cell was placed in an outer packaging foil, the battery was subjected to 120°C baking for 10h, electrolyte was injected, and the lithium ion battery was obtained by formation under restraint pressure.
[0158] 5) Lithium battery test Charging: at room temperature 25±5℃, charge to 3.8V at 1C, rest for 5min, then charge to 3.8V at 0.2C, rest for 1-2h at room temperature. And take a photo; Furnace heating condition: first step: from room temperature, increase to 60℃ at 5℃ / min, keep for 30min. Then continue to increase at 5℃ / min, keep for 30min every 5 degrees Celsius. Until the battery thermal runaway.
[0159] 5, Composite separator crimping: place the composite separator at 25℃ / 80% humidity for 2h, then place it at 25℃ / 50% humidity for 5min, lay the composite separator on a flat table, test the height of the highest point of the composite separator curling from the table.
[0160]
[0161]
[0162] According to the test results in Table 1, the composite aluminum oxide layer is used as the composite separator in the application, the composite separator has better ion conductivity, small thermal shrinkage, strong thermal puncture strength, and improves the thermal runaway temperature of the battery, which can improve the safety performance of the battery.
[0163] In the description of the present application, the terms "first", "second" are only for the purpose of description, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first", "second" can be explicitly or implicitly included at least one of the features. In the description of the present application, the meaning of "a plurality of" is at least two, such as two, three, etc., unless otherwise specifically limited.
[0164] In the description of the present application, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In the present application, the illustrative description of the above terms is not necessarily for the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any suitable manner in any one or more embodiments or examples. In addition, the skilled in the art can combine and combine the different embodiments or features of the embodiments or examples described in the present application without contradiction.
[0165] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limiting the present application, and those skilled in the art can make changes, modifications, replacements and variations to the above embodiments within the scope of the present application.
Claims
1. A composite diaphragm, characterized in that: Comprising a composite alumina layer, the composite alumina layer comprising: a middle aluminum foil, wherein the middle aluminum foil has through holes; A porous aluminum oxide layer is located on at least one side of the middle aluminum foil.
2. The composite diaphragm according to claim 1, characterized in that Also includes: A polymer layer is stacked with the composite aluminum oxide layer.
3. The composite diaphragm according to claim 2, characterized in that The material of the polymer layer includes at least one of polyethylene, polypropylene, aramid, polyvinylidene fluoride, cellulose, polyethylene terephthalate, polyimide, and non-woven fabric.
4. The composite diaphragm according to claim 2 or 3, characterized in that: The polymer layer is located on one side of the composite aluminum oxide layer.
5. The composite diaphragm according to claim 2 or 3, characterized in that: The polymer layers are located on opposite sides of the composite aluminum oxide layer.
6. The composite diaphragm according to claim 5, characterized in that The material of the polymer layer on one side of the composite alumina layer is polyethylene, and the material of the polymer layer on the other side of the composite alumina layer is polypropylene.
7. The composite diaphragm according to claim 2 or 3, characterized in that: The composite aluminum oxide layer is located on opposite sides of the polymer layer.
8. The composite diaphragm according to claim 1, characterized in that The composite alumina layer includes pores, which include large pores and small pores. The small pores are located in the porous alumina layer. The large pores penetrate the middle aluminum foil or penetrate the porous alumina layer on one side of the middle aluminum foil and penetrate into the middle aluminum foil. The diameter φ1 of the large pores and the diameter φ2 of the small pores satisfy: φ2<φ1.
9. The composite diaphragm according to claim 8, characterized in that Meet at least one of the following conditions: The diameter φ1 of the macropore is 5 μm to 50 μm; The diameter φ2 of the small hole is between 20nm and 5μm; The gap I1 between two adjacent macropores is 5 μm to 50 μm; The gap I2 between two adjacent small holes is 30nm~1μm; The coverage rate L1 of the macropores is 5% to 50%; The coverage rate L2 of the small holes is 5% to 60%; The depth H1 of the macropores is the sum of the thickness of the middle aluminum foil and the porous aluminum oxide layer on one side or the thickness of the middle aluminum foil; The depth H2 of the small hole is the thickness of the porous alumina layer on one side.
10. The composite diaphragm according to claim 9, characterized in that Meet at least one of the following conditions: H1 is 0.5μm~5μm; H2 is 0.2μm~5μm.
11. The composite diaphragm according to any one of claims 8 to 10, characterized in that Functional materials are arranged in the pores, and the functional materials include at least one of a solid electrolyte, a lithium supplement material, an organic polymer and a binder.
12. The composite diaphragm according to claim 11, characterized in that The functional material satisfies at least one of the following conditions: The solid electrolyte includes lithium aluminum titanium phosphate; The lithium supplement material includes at least one of Li6CoO4, Li5FeO4, Li2C2O4, and Li2NiO2; The organic polymer includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, and polymethyl methacrylate; The binder includes a granular binder.
13. The composite diaphragm according to claim 2, characterized in that Meet at least one of the following conditions: The thickness of the composite diaphragm is 3 μm to 20 μm; The thickness of the polymer layer is 2 μm to 22 μm; The porosity of the polymer layer is 20% to 70%; The thickness of the intermediate aluminum foil is 0.5 μm to 3 μm; The thickness of the porous aluminum oxide layer is 0.3 μm to 2.5 μm.
14. A method for preparing the composite diaphragm according to any one of claims 1 to 13, characterized in that: include: Using aluminum foil as an anode, performing anodizing on at least one side of the aluminum foil to form an oxide layer on at least one side of the aluminum foil to obtain an anodized product; The anodic oxidation product is subjected to pore-forming treatment to obtain a composite aluminum oxide layer.
15. The method according to claim 14, characterized in that The anodization satisfies at least one of the following conditions: The electrolytic solution for anodization comprises at least one of oxalic acid, phosphoric acid, and sulfuric acid; The cathode of the anodic oxidation comprises a platinum electrode; The current density of the anodic oxidation is 1A / dm 2 ~5A / dm 2 ; The temperature of the anodizing is 0°C to 60°C; The anodizing time is 10 minutes to 10 hours.
16. The method according to claim 14 or 15, characterized in that The pore-forming process includes at least one of chemical etching, focused ion beam etching and laser drilling.
17. The method according to claim 16, characterized in that The pore-forming treatment satisfies at least one of the following conditions: The ion beam current used in the focused ion beam etching is 1pA~50pA; The dwell time of the focused ion beam etching is 50 μs to 1000 μs; The laser frequency used in the laser drilling is 100Hz~1000Hz; The laser drilling speed is 0.5 m / min to 5 m / min.
18. The method according to claim 14, characterized in that Also includes: Functional materials are deposited into the pores of the composite alumina layer.
19. The method according to claim 18, characterized in that The deposition method includes chemical vapor deposition.
20. The method according to claim 14, wherein Also includes: The composite aluminum oxide layer and the polymer layer are composited.
21. The method according to claim 20, characterized in that The compound comprises: The composite alumina layer and the polymer layer are stacked and the obtained stacked product is pressurized to be composited.
22. A battery, characterized in that: The invention comprises the composite diaphragm according to any one of claims 1 to 13 or the composite diaphragm prepared by the method according to any one of claims 14 to 21.
23. A battery pack, characterized in that: The invention comprises the composite diaphragm according to any one of claims 1 to 13, the composite diaphragm prepared by the method according to any one of claims 14 to 21, or the battery according to claim 22.
24. An electrical device, characterized in that: The invention comprises the composite diaphragm according to any one of claims 1 to 13, the composite diaphragm prepared by the method according to any one of claims 14 to 21, the battery according to claim 22, or the battery pack according to claim 23.
Citation Information
Patent Citations
Electrochemical power-supply composite membrane and preparation method thereof
CN103579557A
Electrochemical power supply diaphragm, preparation method thereof and electrochemical power supply
CN103855347A
Lithium ion battery diaphragm and manufacturing method therefor, and lithium ion battery comprising diaphragm
CN106935774A
Negative electrode and diaphragm integrated structure, preparation method of integrated structure and battery comprising integrated structure
CN108630931A
Battery separator and manufacturing method thereof and lithium ion battery
CN110993864A
Cited By
High-lubrication nickel-free hole sealing agent as well as preparation method and application thereof
CN121250498A